2017
DOI: 10.3127/ajis.v21i0.1697
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Measure of Information Security Awareness and the Identification of Bias in Responses

Abstract: The Human Aspects of Information Security Questionnaire (HAIS-Q) is designed to measure Information Security Awareness. More specifically, the tool measures an individual's knowledge, attitude, and self-reported behaviour relating to information security in the workplace. This paper reports on the reliability of the HAIS-Q, including test-retest reliability and internal consistency. The paper also assesses the reliability of three preliminary overclaiming items, designed specifically to complement the HAIS-Q, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…Hence, a clear distinction can be observed between awareness and behaviours. Finally, studies have shown that HAIS-Q has high internal consistency and external reliability (McCormac et al, 2017;Parsons et al, 2014), making it a valid and reliable measurement tool for internet security perceptions and actions.…”
Section: Kab Framework and Hais-qmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, a clear distinction can be observed between awareness and behaviours. Finally, studies have shown that HAIS-Q has high internal consistency and external reliability (McCormac et al, 2017;Parsons et al, 2014), making it a valid and reliable measurement tool for internet security perceptions and actions.…”
Section: Kab Framework and Hais-qmentioning
confidence: 99%
“…Participants respond to each of the items by indicating a score on a five-point Likert scale ("5 = strongly agree", "1 = strongly disagree"). With a total of 31 reverse question items, the HAIS-Q have been consistently found to be a reliable and valid instrument for measuring ISA (McCormac et al, 2017;Parsons et al, 2017;Pattinson et al, 2017). The questionnaire was created and distributed online using one of the biggest local survey platforms, Wenjuanxing, 2 also known as Sojump (Mei & Brown, 2018).…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a significant problem in situations where opinions are solicited, and numerous studies exist on various aspects of applications and ways to address any adverse effects [34]- [36]. Social desirability is also applicable in information security, such as information security behaviour [19] and information security awareness evaluations [37]. The work by [38] is of particular interest as this research study has proved that response bias exists in current scale measurements used in compliance research.…”
Section: Information Security Policiesmentioning
confidence: 99%
“…The perception of risk is personal. In fact, people decide to face or avoid the risk situation in a subjective way ( 14 ). Each activity is based on the perception of risk and its more or less conscious evaluation.…”
Section: The Perception Of Riskmentioning
confidence: 99%